The assignment of functions and intergovernmental fiscal relations in the Philippines twenty years after decentralization - Gilberto M. Llanto (University of the Philippines, School of Economics (UPSE), 2012)
The 1991 Local Government Code devolved substantial spending, taxing, and borrowing powers to local government units. Moving governance closer to the people can generate a welfare gain but local governments must have adequate revenues to finance local development. The paper examines the current status of the tax-expenditure assignment and the intergovernmental fiscal relations, and identifies areas for reform. There is a need for a clearer and more accountable assignment of expenditure by eliminating particular sections of the Code, which serve as a route for national government agencies to be engaged in devolved activities, and for politicians to insert funding for pet projects, which distort local decision making and preferences. There is as well a need to review the tax assignment to improve local revenue generation. The allocation of intergovernmental fiscal transfers may be improved by introducing matching grants to improve equalization transfers to local governments, and performance-based grants to motivate greater local revenue mobilization. Without a clear funding source, unfunded mandates imposed on local governments defeats the purpose of the policy objectives set in those mandates. Local government alliances and cooperative undertaking may be a way to provide public goods with inter-jurisdictional spillover benefits. Consolidation, better coordination of local government activities, and resource pooling for better local service delivery are pathways indicated by successful experiences of LGU collaboration.
Keywords: 330; fiscal ecentralization; tax-expenditure assignment; intergovernmental fiscal relations; performance-based grants; decentralization theorem; Dezentralisierung; Finanzbeziehungen; Kommunale Ausgaben; Dezentralisierung; Philippinen